Detection of Active Matriptase Using a Biotinylated Chloromethyl Ketone Peptide - Godiksen, Sine; Soendergaard, Christoffer; Friis, Stine; Jensen, Jan K.; Bornholdt, Jette; Sales, Katiuchia Uzzun; Huang, Mingdong; Bugge, Thomas H.; Vogel, Lotte K. (PLOS ONE, 2013)
Matriptase is a member of the family of type II transmembrane serine proteases that is essential for development and maintenance of several epithelial tissues. Matriptase is synthesized as a single-chain zymogen precursor that is processed into a two-chain disulfide-linked form dependent on its own catalytic activity leading to the hypothesis that matriptase functions at the pinnacle of several protease induced signal cascades. Matriptase is usually found in either its zymogen form or in a complex with its cognate inhibitor hepatocyte growth factor activator inhibitor 1 (HAI-1), whereas the active non-inhibited form has been difficult to detect. In this study, we have developed an assay to detect enzymatically active non-inhibitor-complexed matriptase by using a biotinylated peptide substrate-based chloromethyl ketone (CMK) inhibitor. Covalently CMK peptide-bound matriptase is detected by streptavidin pull-down and subsequent analysis by Western blotting. This study presents a novel assay for detection of enzymatically active matriptase in living human and murine cells. The assay can be applied to a variety of cell systems and species.